The modern liberty in digital society: data power will set you free - Morente Parra, Vanesa (DERECHOS Y LIBERTADES: Revista de Filosofía del Derecho y derechos humanos, 2021)
Contemporary society brings an immaterial life, in such a way that the citizen is digitized and learns to exchange information in a virtual network of planetary dimension. An inexhaustible world of information and communication opens up in front of us, however its price can be very high: our freedom. The theoretical model of “modern liberty” announced by Benjamin Constant, it`s used here like an analytical criteria of the digital liberty. Is modern liberty possible in digital society? Is it possible to understand the internet as a democratic society? Should we move towards another model of liberty? This article wants to answer these questions.
Keywords: liberty; personal determination; data and digital society